Meaning Makers and Secularization: Human Rights as an Expression of Meaning in a Post-Secular Age - Montgomery, Cameron (2012)
The connection between secularization theory, the privatization of religion and the public development of rights legislation is a response to growing confusion concerning the place of ‘morality’ and ethics in a public, ‘secularized’ society. This paper explores how human rights legislation emerged in the ‘western’ context, how it has adapted to globalization and criticisms it faces. Brief examples of Jainism and the Inuit represent alternative rights paradigms, acting as a cautionary against solidifying the Universal Declaration of Human Rights into an inflexible document universalizing all cultures. I conclude that it is important for ‘secular’ societies to make choices in public policy with a critical and judicious examination of the citizens’ rights in mind, not only to preserve rights historically achieved but to prevent ambiguous or indecisive ethical positions from resulting in the protection of corporate interest above the individual.